Developing the inter-role conflict scale for eye-care workers - N.V. Rodina; B.V. Biron; A.I. Ukhanova; N.S. Semeniuk; A.V. Kernas (Ukrainian Society of Ophthalmologists, 2020)
Background: Eye care workers are highly prone to the risk of psychological problems due to emotional demands of job and high stress loads. Because inter-role conflicts act as stress load factor, it is important to develop psychometrically adapted psychodiagnostic instruments for detecting them. Purpose: To develop a Ukrainian version of the psychometric scale as a tool for measuring inter-role conflicts for eye care workers, to psychometrically analyze it, and to estimate its relationships with stress reactions. Material and Methods: The study sample consisted of the eye care workers from the Filatov institute. Two hundred and eleven eye care workers were requested to respond to relevant questions. The response rate was 85.8% (181/211). The 181 responders included 99 nursing staff members and 82 ophthalmologists. The adapted version of the 1996 Netemeyer's et al Work-Family Conflict and Family-Work Conflict Scales and the Stress Reaction Inventory for eye care workers designed by Ukrainian researchers, Tsekhmister, Daniliuk, Rodina, Biron, and Semeniuk, were used in the study. Results: The Inter-role Conflict Scale was developed by adapting the Netemeyer's et al questionnaire. The modified version of the scale is comprised of the two subscales describing two forms of inter-role conflicts, Work-Family Conflict (WFC) and Family-Work Conflict (FWC); these subscales were found to have high internal consistency and test-retest reliability. The two-factor scale model was verified by a confirmatory factor analysis. The two forms of inter-role conflicts were found to be statistically more severe in the physician staff than in the nursing staff. The test norms were developed and presented using the quartile scale, as long as the sample was representative. Therefore, the adapted Ukrainian-language version of the Inter-role Conflict Scale for eye care workers showed evidence of internal consistency and construct validity.